2004
DOI: 10.1016/s0014-5793(04)00049-3
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fish oil up‐regulates cholesterol 7α‐hydroxylase mRNA in mouse liver leading to an increase in bile acid and cholesterol excretion

Abstract: To investigate the molecular events controlling reverse cholesterol transport, we compared gene expression of normal mouse liver to that of mice fed a long chain (LC) g g-3 fatty acid-enriched diet. Using cDNA microarrays, we assessed expression levels of 1176 genes, and we found that D-site binding protein (DBP) was three-fold increased in mice on a LC g g-3 fatty acid-rich diet compared to controls. DBP is known to increase transcriptional level of cholesterol 7K K-hydroxylase (C7K K), the rate-limiting enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 28 publications
3
28
1
1
Order By: Relevance
“…CYP7A1 is induced by PPAR/RXR or LXR/RXR, but is inhibited by PPAR/LXR 39) . Fish oil stimulates RXR alpha expression markedly more than LXR 36) . This observation suggests that EPA induces RXR mRNA more than DHA and that the marked increase of CYP7A1 mRNA expression in the MO diet with fenofibrate group in this study was induced by formation of a PPAR/RXR or LXR/RXR combination from the induction of RXR and PPAR by EPA and fenofibrate, respectively.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…CYP7A1 is induced by PPAR/RXR or LXR/RXR, but is inhibited by PPAR/LXR 39) . Fish oil stimulates RXR alpha expression markedly more than LXR 36) . This observation suggests that EPA induces RXR mRNA more than DHA and that the marked increase of CYP7A1 mRNA expression in the MO diet with fenofibrate group in this study was induced by formation of a PPAR/RXR or LXR/RXR combination from the induction of RXR and PPAR by EPA and fenofibrate, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…The data presented here indicate that the increment of the plasma total cholesterol level in fenofibrate-supplemented groups is due to the increase of the plasma HDL-cholesterol level ( Table 2). Fish oil up-regulates CYP7A1 as well as increasing bile acid and cholesterol excretion 36) . Furthermore, fenofibrate induces CYP7A1 expression through PPAR 37,38) .…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that 4.5% fish oil in the butter blend does not play an important role in acute cholesterol absorption. It has however been shown that n-3 PUFA via effects on transcription factors can upregulate 7a-hydroxylase mRNA in mouse liver leading to an increase in bile acid and cholesterol excretion [35]. Therefore it cannot be rule out that a long-term consumption of the butter blend containing fish oil may affect the cholesterol levels in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…The fecal excretion of bile acids in the CϩEX and DF/KBRϩEX groups was significantly higher than that in the C group. It has been reported that dietary fish oil increases the level of hepatic CYP7A1 mRNA in mice (35) and that the enzyme activity of CYP7A1 correlates with the increase in the mRNA level (36). Fish oil enhances bile acid synthesis in rats (37) suggesting that bile acid synthesis would be increased in the EX and DF/KBRϩEX groups in comparison to the C group.…”
Section: Discussionmentioning
confidence: 99%